The Relationship between Landing Error Scoring System Performance and Injury in Female Collegiate Athletes - Peter Lisman; Joshua N. Wilder; Joshua Berenbach; Enric Jiao; Bethany Hansberger (North American Sports Medicine Institute, 2021)
# Background The Landing Error Scoring System (LESS) is a standardized tool used to identify aberrant biomechanical movement patterns during a jump-landing task. Prior authors have examined the value of the LESS in identifying ACL injury risk in athletic populations. Yet, no study has evaluated the association between LESS performance and incidence of any type of lower extremity injury in female collegiate athletes across multiple sports. # Purpose The purpose of this study was to examine the association between LESS performance as measured with a markerless motion-capture system and lower extremity injury in female collegiate athletes. # Study Design Prospective cohort study. # Methods One hundred and ten DI female collegiate athletes (basketball, n=12; field hockey, n=17; gymnastics, n=14; lacrosse, n=27; softball, n=23; volleyball, n=17) completed a jump-landing test prior to the start of their sport seasons. The LESS was automatically scored using a Microsoft Kinect sensor and Athletic Movement Assessment software (PhysiMax®). Participants were tracked throughout one competitive season for incidence of time-loss lower extremity injury. A Receiver Operating Characteristic curve determined the optimal cutpoint for the total LESS score for predicting injury. Pearson's Chi squared statistics examined the association between injury and LESS total scores >5. The Fisher exact test evaluated group differences for the frequency of receiving an error on individual LESS test items. # Results Female collegiate athletes with LESS scores >5 were not more likely to be injured than those with scores ≤5 (χ2=2.53, p=0.111). The relative risk of injury to this group was 1.78 (95% CI=0.86, 3.68) while the odds ratio was 2.10 (95% CI=0.83, 5.27). The uninjured group was more likely to receive an error on lateral trunk flexion at initial contact than the injured group (p=0.023). # Conclusion The LESS total score was not associated with an increased odds of lower extremity injury in this cohort of female collegiate athletes. Future studies to examine the association between individual LESS item scores and injury are warranted. # Level of Evidence 1b.